Children's Language and Communication Difficulties / Understanding, Identification and Intervention - Dockrell Julie (London Cassell, 1999)
The Authors examine the problems of identification and diagnosis, and explore the range of physical and cognitive disabilities associated with language problems. Acknowledgements, Preface, The Development of Communication and Language, Mechanisms of Language Development, Specific Speech and Language Disorders, Learning Disabilities and Language Difficulties, Sensory Isolation and Visual Impairments, Hearing Impairments, Identifying and Assessing Language Problems, Intervention, Difficulties with Language and Communication: Identification and Understanding and Intervention, References and Further Reading, Name and Subject Index.